RSM01, a novel respiratory syncytial virus monoclonal antibody: preclinical characterization and results of a first-in-human, randomised clinical trial - Aurelio Bonavia; Micha Levi; Harald Rouha; Adriana Badarau; Jonne Terstappen; Shayne Watson; Aparna B. Anderson; Joleen T. White; Jintanat Ananworanich; Dale Taylor; Andrijana Radivojevic; Michael Shaffer; et al. (BMC Infectious Diseases)
Abstract Background Respiratory syncytial virus (RSV) is a leading cause of lower respiratory tract disease among infants and young children worldwide, especially in low- and middle-income countries (LMICs). RSM01 is a novel, highly potent, half-life-extended anti-RSV monoclonal antibody (mAb) candidate primarily being developed for LMICs. Here we present the preclinical characterisation and results of a phase 1 trial of RSM01. Methods Preclinical characterisation of RSM01 was conducted using in-vitro neutralization assays and cotton rat models. In the first-in-human, double-blind, phase 1 trial, 56 healthy adults were randomised 6:1 within dose cohorts to receive a single dose of RSM01 (n = 48) or placebo (n = 8): 300 mg intravenously (IV), 300 mg intramuscularly (IM) or 1000 mg IV (parallel cohorts), 3000 mg IV, and an expansion cohort of 600 mg IM. Systemic solicited adverse events (AEs) were assessed through day 7; unsolicited AEs were collected through day 151. Pharmacokinetics and anti-drug antibodies (ADA) to RSM01 were assessed using immunoassays. A population pharmacokinetics model predicted paediatric pharmacokinetics parameters using allometric scaling and age-specific population weight statistics of North American and African infants. Results RSM01 exhibited highly potent neutralizing activity in the single ng/mL range (0.7–6.4) against diverse RSV-A and RSV-B isolates in vitro. RSM01 also demonstrated prophylactic efficacy in cotton rat models with both RSV subtypes. In the phase 1 clinical trial, the most common unsolicited AEs were COVID-19 (2/48), headache (2/48), and nausea (2/48), all in RSM01-treated participants. The only systemic solicited AEs reported were headache (5/48) and tiredness (2/48) in participants receiving RSM01. No serious AEs or deaths were reported. The half-life of RSM01 was 78 days with dose-proportional increases in Tmax and AUClast after IV administration. Among RSM01-treated participants, 2/48 were ADA positive at baseline, and 1/48 seroconverted to ADA-positive post-baseline. Conclusions RSM01 is a highly potent, half-life-extended, RSV-neutralising mAb candidate that was shown to be well tolerated in healthy adults. The rate of ADA to RSM01 was low. The long half-life of RSM01 and pharmacokinetics profile support further development of RSM01 as a potential single dose per season prophylaxis to prevent RSV disease in infants. Trial registration Clinicaltrials.gov NCT05118386, Nov 12, 2021.